The effect of complexing agents in chemical solution deposition of metal chalcogenide thin films. (21st January 2021) - Sengupta, Sucheta; Aggarwal, Rinki; Golan, Yuval
Abstract : This review article gives an overview of different complexing agents used during chemical deposition of metal chalcogenide thin films and their role in controlling the resultant morphology by effective complexation of the metal ion. Abstract : Among the chemical deposition methods to produce thin films, chemical deposition from aqueous solution (CD) is the oldest and most studied process in which the substrate is exposed to soluble precursors which react or decompose to produce the desired thin film material. An intricate balance of growth parameters is necessary to produce a good quality film. The presence of complexing agents ensures effective complexation of the metal cation in solution, leading to its slow release for preventing bulk precipitation. Here, we provide a comprehensive overview of the different complexing agents used to achieve control over the resultant morphology of CD metal chalcogenide thin films.